A species specific simplex polymerase chain reaction-based approach for detection of goat tallow in heat clarified milk fat (ghee). (18th December 2017) - Hazra, Tanmay; Sharma, Vivek; Sharma, Rekha; Arora, Sumit
ABSTRACT: The detection of milk fat adulteration with foreign fats/oils continues to be a challenge for the dairy industry as well as food testing laboratories. Recently, various chromatographic methods have been developed to detect a low level of vegetable oil in ghee but detection of animal body fat in ghee is still a challenge. In India, goat body fat (goat tallow) adulteration in ghee is a very serious problem. In the present investigation, a rapid species specific polymerase chain reaction (PCR)-based methodology has been standardised to detect goat tallow in heat clarified milk fat (ghee). This standardised PCR-based protocol did not show any false positive results in the genuine ghee (heat clarified butter fat) samples. Adulteration of ghee (both cow and buffalo) with goat tallow at the 10% level could be detected using the standardised PCR-based protocol. The protocol standardised is rapid and convenient to use.